ANALISIS PERBANDINGAN LAPORAN TAHUNAN PT. BANK NEGARA INDONESIA (PERSERO) SEBELUM DAN SESUDAH MENJADI PEMENANG ANNUAL REPORT AWARD (ARA) 2017 - Rizky Nikmatul Wakhidah; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT             This research was conducted to determine the differences in the annual Indonesian state bank financial report (BNI) before and after the annual report award (ARA). This research was conducted at a company that won an award in the annual report award (ARA) 2017. The research data uses secondary data, the focus of this study is to describe the financial statements contained in Bank BNI's annual report using four categories: liquidity ratios, activity ratios , debt ratio, and profitability analysis. The data used in this study is a quantitative descriptive test. The test results show that the increase in fixed assets and current liabilities of Bank BNI at each ratio differs inconsistently from increasing.Keywords: Annual Report Award, Financial Ratios, Descriptive Statistics.